Exploring standardisation, monitoring and training of medical devices in assisted vaginal birth studies: protocol for a systematic review. Issue 4 (14th April 2019) - Hotton, Emily J; Renwick, Sophie; Barnard, Katie; Lenguerrand, Erik; Wade, Julia; Draycott, Tim; Crofts, Joanna F; Blencowe, Natalie S
Abstract : Introduction: Assisted vaginal birth (AVB) can markedly improve maternal and neonatal outcomes arising from complications in the second stage of labour. Historically, both forceps and ventouse devices have been used to assist birth; however, they are not without risk and are associated with complications, such as cephalohaematoma, retinal haemorrhage and perineal trauma. As new devices are developed to overcome the limitations of existing techniques, it is necessary to establish their efficacy and effectiveness within randomised controlled trials (RCTs). A major challenge of evaluating complex interventions (ie, invasive procedures/devices used to assist vaginal birth) is ensuring they are delivered as intended. It can be difficult to standardise intervention delivery and monitor fidelity, and account for the varying expertise of clinicians (accoucher expertise). This paper describes the protocol for a systematic review aiming to investigate the reporting of device standardisation, monitoring and training in trials evaluating complex interventions, using AVB as a case study. Methods and analysis: Relevant keywords and subject headings will be used to conduct a comprehensive search of MEDLINE, Embase, Cochrane Central Register of Controlled Trials, Cumulative Index of Nursing and Allied Health Literature and ClinicalTrials.gov, for RCTs and pilot/feasibility studies evaluating AVB. Abstracts will be screened and full-text articles of eligible studies reviewed for inclusion. Information relating to the following categories will be extracted: standardisation of device use (ie, descriptions of operative steps, including mandatory/flexible parameters), monitoring of intervention delivery (ie, intervention fidelity, confirming that an intervention is delivered as intended) and accoucher expertise (ie, entry criteria for participation, training programmes and previous experience with the device). Risk of bias of included studies will be assessed. Ethics and dissemination: Ethical approval is not required because primary data will not be collected. Findings will be disseminated by publishing in a peer-reviewed journal and presentations at relevant conferences.